Terjemahan tafsir ayat ahkam Ash Shabuni - Muhammad Ali Ash_Shabuni (Bina Ilmu, 1985)
Oen, Jil 1=c.1-3 Jil. 2=C.1-4 Jil.3= C.1-4 / ir, jil.1,c.4; sn,jl.1,c.5-6, jl.2,c.5-6, jl.3,c.5/en, jil.1=c.4/tr, jil.3=c.6-8/nr,jil.2=.C.7-8